PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA SMA KELAS XI IPS JAWAAHIRUL HIKMAH 3 TULUNGAGUNG - ihdo rahmandani (Jupeko (Jurnal Pendidikan Ekonomi), 2023)
The method (Guided inquiry) is learning that explains procedure experimental by involving the ability of students who are as a learning subject that needs toinvolved be activelyin the learning process, while the teacher is only a facilitator by providing guidance along with guidance from the teacher to students in conducting themethod guided inquiry guided In accordance with the title and research objectives, the data obtained in the form of numbers and analysis using statistical analysis. Seen from the data analyzed, this type of research is quantitative, the research sample is all XI IPS class at SMA Jawaahirul Hikmah 3 Tulungagung, totaling 35 student. With data collection techniques using tests. Based on the results of data analysis that has been carried out, processed, and analyzed, The results of the t test analysis are known to be the value of Sig. (2-tailed) is 0.000 0.05, then rejected and accepted. from the results of the t test got a value of 31,399. with the significant value of is 0.05 then 1,692 . So it can be concluded that . In other words, the treatment carried out in the research have a significant effect on theresults expected, namely there is significant influence between GuidedLearning Model Inquiry Against Ability of Thinking Critical Class XI Students of SMA Jawaahirul Hikmah 3 Tulungagung.Keywords: Critical Thinking Ability, Guided Inquiry